+0  
 
0
1041
2
avatar

Suppose a and b are integers. How many solutions are there to the equation ab = 2a + 3b?

 Sep 27, 2017
 #1
avatar
0

a*b=2a + 3b

a = -3 and b = 1

a = 0 and b = 0

a = 1 and b = -1

a = 2 and b = -4

a = 4 and b = 8

a = 5 and b = 5

a = 6 and b = 4

a = 9 and b = 3

 Sep 27, 2017
 #2
avatar+98044 
+1

ab  = 2a + 3b

 

Square both sides

 

a^2b^2  = 4a^2 + 12ab + 9b^2   rearrange as

 

[ 4-b^2]a^2 + [ 12b]a + 9b^2  = 0

 

Setting this up as a quadratic and solving for  a, we have that

 

a  =  -12b ±√ [  (-12b)^2 - 4 (4 - b^2)( 9b^2) ]

        ________________________________

                    2 [ 4 - b^2]

 

a  =  -12b ±√ [  144b^2  - 144b^2  + 36b^4 ]

        _______________________________

                      2 [ 4 - b^2 ]

 

a =    -12b  ± 6b^2

          ___________

              2 [ 4 - b^2 ]

 

 

a  =     6b [  -2  ± b ]

           ___________

             2 [ 4 - b^2 ]

 

a  =   3b [ -2  ± b ]

        _____________         

          (2 + b)  (2 - b)

 

Choosing        a  =       3b [ -2 - b]                           -3b [ 2 + b]                     -3b

                                  __________     =                _____________      =        ___

                                  (2 + b) (2 -b)                         (2 + b) (2 -b)                    2 -b

 

Will  produce all the possible integer answers                       

 

 

Simplifying, we have that            

 

                                                                                                                            

a  =  -3b               3b                                     

       _____   =     ____                                                                            

        2 - b             b - 2                   

 

 

Dividing this fraction produces :

 

a =   3  +    6                                                                                                      

               ____                                                                              

                b - 2                                                                                       

 

And when   b  =     8      5      4     3    1    0    -1   -4

                   a =      4      5      6     9   -3    0     1    2

 

So.........( a, b)  =  (2, -4), (1, -1), (0, 0), (-3, 1), (9, 3), (6,4), (5,5)  and (4,8)

 

 

 

cool cool cool

 

 

                  

 

 

a  = 

 Sep 27, 2017
edited by CPhill  Sep 27, 2017

8 Online Users